The socio-economic impact of the establishment and development of Jerera growth point in Masvingo province since 1988 - Jeke, Kudzai (Midlands State University, 2017)
The research focused on the socio-economic impacts of the establishment and development of growth points in Zimbabwe. Jerera was used as a case study to depict these socio-economic impacts. The study sought to analyze to what extent the establishment of growth points have affected the rural livelihoods. A qualitative research design was used in the research and interviews and questionnaires were used as data mining tools. A review of literature was conducted with the aim of helping fill in the existing gap and getting a broader understanding of the socio-economic impacts of growth points in Zimbabwe and elsewhere. The findings show that despite the intended positive impacts, the establishment and development of Jerera growth point brought in socio-economic problems to the people of Zaka district